Repatriation, science and identity
1 online resource (xxi, 269 pages)
Keywords: "Repatriation, Science, and Identity explores the entanglement of race, history, identity and ethics inherent in the application of scientific techniques to determine the provenance of Indigenous Ancestral Remains in repatriation claims and processes. The book considers how these issues relate to collections of Indigenous skeletal remains, but also their resonance with emerging concerns about the relatively unknown history of scientific interest in Indigenous hair and blood samples. It also explores the more recent practice of sampling for the purposes of DNA analysis, and issues concerning the data that has been produced from all of the above types of research. Placing recent interest in applying scientific techniques to repatriation in their historical context, it enables discourses of identity and scientific authority, an assessment their efficacy, and an exploration of ethical and practical challenges and opportunities. In doing so, this book reveals new histories about scientific interest in Indigenous biology and the collections that resulted, as well as providing reflection for all repatriation practitioners considering scientific investigation when faced with the challenges inherent in the repatriation of unprovenanced or poorly provenanced Ancestral Remains. Providing reader with the means to assess the value, or otherwise, of the scientific information they may encounter, Repatriation, Science, and Identity is an invaluable resource for researchers and professionals working with Indigenous Ancestral Remains"--